Akad Jual Beli Dalam Transaksi Online Pada Aplikasi Grab-Food Ditinjau Dari Fikih Muamalah - Miftahul Jannah; Sabbar Dahham Sabbar (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
This study aims to analyze the suitability of contracts in online transactions on the Grab-Food application with the principles of muamalah fiqh. In this application-based food delivery transaction, three types of contracts used are rental contracts, sale and purchase contracts, and wakalah contracts. The rental contract occurs between the application provider company and the driver and seller, while the sale and purchase contract is between the user (buyer) and the food seller. In addition, the wakalah contract occurs when the user gives the driver power to complete the purchase and delivery of food. The results of the study show that each contract has fulfilled the pillars and requirements of sharia, where the roles and responsibilities of each party have been clearly regulated, thereby reducing the potential for ambiguity (gharar) in the transaction. This finding supports previous studies and strengthens the concept of flexible muamalah fiqh that can be applied in various forms of digital transactions. The study concludes that app-based transactions such as Grab-Food can be adjusted to remain compliant with sharia values, providing confidence for Muslim consumers in conducting halal digital transactions. Recommendations for further research include analysis of blockchain technology to strengthen transparency in online transactions.